Accuracy of arch expansion with two thermoplastic materials in Invisalign® patients: EX30® and SmartTrack® - Raquel Bueno MEDEIROS; Renata Faria SANTOS; Jose Augusto MENDES-MIGUEL; Eduardo Kant Colunga ROTHIER; Fausto Medeiros MENDES; Gladys Cristina DOMINGUEZ (Dental Press Editora, 2024)
ABSTRACT Objective: The purpose of this retrospective study was to compare accuracy of arch expansion using two different thermoplastic materials in Invisalign aligners: EX30® (Polyethylene Terephthalate Glycol, or PETG) and SmartTrack® (polyurethane). Methods: The study sample comprised 65 adult patients consecutively treated with Invisalign from two private practices: group 1 - treated with EX30® (358 teeth) and group 2 - treated with SmartTrack® (888 teeth). Six hundred and twenty-three measurements were assessed in three digital models throughout treatment: model 1 - initial, model 2 - predicted tooth position, and model 3 - achieved position. Sixteen reference points per arch were marked and, after best alignment, 2 points per tooth were copied from one digital model to another. Linear values of both arches were measured for canines, premolars, and first molars: on lingual gingival margins and cusp tips of every tooth. Comparisons were performed by Wilcoxon and Mann-Whitney test. Results: Both termoplastic materials presented significant differences between predicted and achieved values for all measurements, except for the lower molar cusp tip in the SmartTrack® group. There is no statistical difference in the accuracy of transverse expansion between these two materials. Overall accuracy for EX30® aligners in maxilla and mandible were found to be 37 and 38%, respectively; and Smarttrack® presented an overall accuracy of 56.62% in the maxilla and 68.72% in the mandible. Conclusions: It is not possible to affirm one material expands better than the other. Further controlled clinical studies should be conducted comparing SmartTrack® and EX30® under similar conditions.